129k views
4 votes
Which of the following expressions is a sixth root of unity?

-1
i
-i
all of the above

User Nkchandra
by
7.1k points

2 Answers

1 vote

Answer:

-1

Explanation:

User Recur
by
6.4k points
0 votes

Let sixth root of unity be x

So
x^(6)=1


x^6-1=0


(x^3)^2-1^2=0


(x^3-1)(x^3+1)=0
x^3-1=0 $ or $ x^3+1=0


(x-1)(x^2+x+1)=0 $ or $ (x+1)(x^2-x+1)=0
x-1=0 $ or $ x^2+x+1=0 $ or $ x+1=0 $ or $ x^2-x+1=0

Using Quadratic formula for the quadratic equations we get


x=1 $ or $ x=(-1\pm√(1-4) )/(2) $ or $ x = -1 $ or $ x=(1\pm√(1-4) )/(2)


x = 1 $ or $ x=(-1\pm√(3)i )/(2) $ or $ x = -1 $ or $ x=(1\pm√(3)i )/(2)

Only 1, out of the given option is the sixth root of unity.

User Victoria Ruiz
by
5.8k points